2009
DOI: 10.1074/jbc.m109.039453
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Loading Regulates NFATc1 and β-Catenin Signaling through a GSK3β Control Node

Abstract: Mechanical stimulation can prevent adipogenic and improve osteogenic lineage allocation of mesenchymal stem cells (MSC), an effect associated with the preservation of ␤-catenin levels. We asked whether mechanical up-regulation of ␤-catenin was critical to reduction in adipogenesis as well as other mechanical events inducing alternate MSC lineage selection. In MSC cultured under strong adipogenic conditions, mechanical load (3600 cycles/day, 2% strain) inactivated GSK3␤ in a Wnt-independent fashion. Small inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(151 citation statements)
references
References 69 publications
7
142
1
Order By: Relevance
“…This is in agreement with in vitro studies on the preadipocyte cell line ST2 (15) and is in line with studies on sustained expression of b-catenin by expression of Wnt10b in preadipocytes or following stimulation by mechanical loading, where adipogenesis is blocked in favor of osteogenesis. (13,24,25) Of interest is our data on osteoclast maturation and activation. In contrast to what was reported by Glass and colleagues, (20) where it was shown that Wnt signaling promoted the ability of differentiated osteoblasts to inhibit osteoclast differentiation, we have shown a transient increase in the number of TRACP þ osteoclasts, most likely owing to an increase in the number of hematopoietic progenitors, from which osteoclasts are derived.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with in vitro studies on the preadipocyte cell line ST2 (15) and is in line with studies on sustained expression of b-catenin by expression of Wnt10b in preadipocytes or following stimulation by mechanical loading, where adipogenesis is blocked in favor of osteogenesis. (13,24,25) Of interest is our data on osteoclast maturation and activation. In contrast to what was reported by Glass and colleagues, (20) where it was shown that Wnt signaling promoted the ability of differentiated osteoblasts to inhibit osteoclast differentiation, we have shown a transient increase in the number of TRACP þ osteoclasts, most likely owing to an increase in the number of hematopoietic progenitors, from which osteoclasts are derived.…”
Section: Discussionmentioning
confidence: 99%
“…Loading controls b-catenin levels by regulating phosphorylation of GSK3, thereby inhibiting b-catenin degradation and increasing its levels in the cytoplasm; thus, driving osteoblastic differentiation (14,103). The Wnt signals are reported to be transduced through the Lrp 5/ 6 receptor; thus, mutations in this receptor results in a constitutive ''ON'' signal, leading to a state of high bone mass (10,55,69), while loss of function mutations in the Lrp5 receptor lead to poor mechanical response to loading (70,101).…”
Section: Wnt (Wingless) Signalingmentioning
confidence: 99%
“…For instance, MSCs can be differentiated into adipocytes by stimulation with bone morphogenetic protein (BMP) 4 (Tang et al, 2004), and into osteoblasts or chondrocytes by treatment with BMP2 (Noël et al, 2004). In addition to soluble factors, MSC lineage specifications can be directed by physical changes induced by the extracellular environment, including cell area and strain, and by extracellular matrix (ECM) stiffness (Dupont et al, 2011;Engler et al, 2006;McBeath et al, 2004;Nobusue et al, 2014;Sen et al, 2009;Swift et al, 2013). MSCs cultured on soft substrates differentiate into adipocytes efficiently, whereas cells on rigid substrates preferentially differentiate into osteoblasts (Dupont et al, 2011;Engler et al, 2006).…”
Section: Introductionmentioning
confidence: 99%